Negative impact of roadside mowing on arthropod fauna and its reduction with ‘arthropod‐friendly’ mowing technique - Steidle, Johannes L. M.; Kimmich, Thomas; Csader, Michael; Betz, Oliver (Journal of applied entomology (1986), 2022)
An underestimated factor that contributes to the decline of insects observed during the last year is probably the mortality, which is caused by mowing of grassland. We studied the negative impact of mowing on the arthropod fauna of roadside grassland, which might serve as potential habitat for insects to prevent their local extinction and as corridor for the dispersal in anthropogenic landscapes. In addition, we studied if losses due to mowing can be mitigated by the use of ‘arthropod‐friendly’ mowing technique. In agreement with earlier studies, we found that mowing with a conventional mowing head (MK 1200 from MULAG) caused considerable losses in arthropods, ranging from 29% for Heteroptera over around 50% in Araneae, Cicadina, Hymenoptera and Diptera, up to 73% for holometabolous larvae, and 87% for Lepidoptera. These losses by mowing were fully offset for Araneae, Cicadina, Heteroptera, Lepidoptera and larvae of holometabolous insects when using the mowing head Eco 1200 from MULAG, which was designed to be ‘arthropod‐friendly’. For Hymenoptera and Diptera, the losses were reduced by 15% and 25% respectively. For Saltatoria and Coleoptera, we did not find any significant differences between all treatments. These data demonstrate that mowing of roadsides with conventional mowing technology has a highly detrimental effect on the grassland arthropod fauna. However, this effect can be offset or at least mitigated by the use of ‘arthropod‐friendly’ mowing technique. Therefore, this technique has a high potential to reduce insect decline in roadside grassland, making these areas a habitat for insects.